The cost and cost efficiency of conducting a 24-h dietary recall using INDDEX24, a mobile dietary assessment platform, compared with pen-and-paper interview in Viet Nam and Burkina Faso. Issue 3 (14th February 2023) - Adams, Katherine P.; Bell, Winnie; Somé, Jérome W.; Colaiezzi, Brooke; Wafa, Sarah; Rogers, Beatrice; Coates, Jennifer
Abstract: The INDDEX24 Dietary Assessment Platform (INDDEX24) was developed to facilitate the collection of 24-h dietary recall (24HR) data. Alongside validation studies in Viet Nam and Burkina Faso in 2019–2020, we conducted activity-based costing studies to estimate the cost of conducting a 24HR among women of reproductive age using INDDEX24 compared with the pen-and-paper interview (PAPI) approach. We also modelled alternative scenarios in which: (1) 25–75 % of dietary reference data were borrowed from the INDDEX24 Global Food Matters Database (FMDB); (2) all study personnel were locally based and (3) national-scale surveys. In the primary analysis, in Viet Nam, the 24HR cost US 111 004 (755/respondent, n 147) using INDDEX24 and 120 483 (820/respondent, n 147) using PAPI. In Burkina Faso, the 24HR cost 78 105 (539/respondent, n 145) using INDDEX24 and 79 465 (544/respondent, n 146) using PAPI. In modelled scenarios, borrowing dietary reference data from the FMDB decreased the cost of INDDEX24 by 17–34 % (Viet Nam) and 5–15 % (Burkina Faso). With all locally based personnel, INDDEX24 cost more than PAPI (498 v . 448 per respondent in Viet Nam and 456 v . 410 in Burkina Faso). However, at national scales ( n 4376, Viet Nam; n 6500, Burkina Faso) using all locally based personnel, INDDEX24 was more cost-efficient (109 v . 137 per respondent in Viet Nam and 123 v . 148 in Burkina Faso). In two countries and under most circumstances, INDDEX24 was less expensive than PAPI. Higher INDDEX24 survey preparation costs (including purchasing equipment) were more than offset by higher PAPI data entry, cleaning and processing costs. INDDEX24 may facilitate cost-efficient dietary data collection.